Understanding T cell Immunity in Atopic Dermatitis: Relevance to Staphylococcus aureus Vaccine Design - Clowry, Julianne (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
In this thesis, I present original research investigating the T cell response to S. aureus in paediatric atopic dermatitis (AD). The aim of this study is to investigate the memory T cell immune response to S. aureus in two cohorts of AD subjects with and without cutaneous S. aureus skin infection, compared to healthy controls. This is achieved via the analysis of circulating and S. aureus antigen-specific systemic immune responses in conjunction with cutaneous cytokine T cell profiles. The primary purpose is to advance progress in the development of novel targeted therapeutics, including an anti-S, aureus vaccine in AD patients severely impacted by S.aureus skin infections. Atopic dermatitis is a common, complex inflammatory skin disease characterised by epidermal barrier dysfunction, immune dysregulation and microbiome alteration with the latter, particularly S. aureus, increasingly recognised as a key factor in disease pathogenesis. Identifying correlates of cellular T cell immunity in high-risk patient cohorts is now considered an essential prerequisite for successful anti-S.aureus vaccine development in humans, following reviews of previous S. aureus vaccine failures. Blood samples and stratum corneum tape-strips were collected from patients with AD and healthy controls, to evaluate site-specific immunological responses to this pathobiont. We identify a systemic and cutaneous immunological signature associated with S. aureus skin infection (ADS.aureus) in a paediatric AD cohort, using a combined multinomial Bayesian analysis. ADS.aureus was most highly associated with elevated cutaneous chemokines IP10 and TARC, which preferentially direct Th1 and Th2 cells to skin. Systemic CD4+/CD8+ T cells, except for Th2 cells had reduced expression in ADS.aureus, particularly circulating Th1, memory IL10 and skin-homing memory Th17 cells. Systemic γδ T cell expansion in ADS.aureus was also observed. This distinct immunological signature, characterising the host response to S.aureus skin infection in AD, provides new directions for future targeted treatments in this susceptible population.
APPROVED
Keywords: atopic dermatitis; Staphylococcus aureus; T cell